A way of life: Indigenous perspectives on anti oppressive living - Thomas, Robina; Green, Jacquie (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
The focus of this article is on the key elements of anti oppressive practices as examined by two Indigenous women who practice and teach anti-oppressive ways. Anti oppressive living is characterized as a “Way of Life” that values the sacred and traditional teachings of various Indigenous cultures. The medicine wheel is discussed and highlighted as an effective teaching tool to examine antioppressive ways of living, practicing and perspectives.